TAFSIR AYAT-AYAT NEUROSAINS DAN AYAT-AYAT BERAKHIRAN AFALAA TA’QILUUN - Heru Widi Widodo (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2019)
The advantage of humans and other creatures is that they are able to function the mind. As with other beings, God is also gifted with reason. Reason can also be called neuroscience. Humans are "hayawanunna thiq" or thinking animals, wherein the Creator of man is given the mandate to prosper the earth as "khalifah fil ard". As a caliph must be smart-minded or truly maximize his brain and mind as well as possible and also not a liar. As in the Qur'an Surat al-Alaq [96]: 15-16. In addition to discussing the brain or reason it also shows its connection with the verse that ends, "afalaa ta’qiluun" also verses that end, "afalaa yatadzakkaruun". This paper wants to revive the function of humans as noble beings who have been equipped with extraordinary intelligence by Allah. With the brain that God has designed in such a way, is mankind going to take responsibility as the noblest creature, also whether humans will only become natural destroyers that God has given to humans to manage it?